Disaster risk governance in Iran: Document analysis - Mehdi Safari; Hesam Seyedin; Katayoun Jahangiri (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Disaster risk is a product of a combination of hazard, exposure, and vulnerability. Governance in the health system is a multifaceted sphere, with political, economic, and legal dimensions. Disaster risk governance is an analytical framework employed for assessing the capacity of institutional governance. This study has been conducted to investigate the current status of national strategy documents concerned with disaster risk governance in Iran through document analysis. MATERIALS AND METHODS: The investigated documents were collected through requests from the secretariat and the archives. 102 documents were analyzed. Twelve documents in the domain of accountability, 7 in participation, 9 in state and nonstate actor, 14 in knowledge sharing, 21 in sustainable developments, and 19 documents in integrated risk management were analyzed. The process of analysis included selecting documents and evaluating and analyzing them by content analysis method. RESULTS: Documents coded according to the main areas of policymaking in disaster risk governance were analyzed, and sub-component and related topics were deduced in each domain. The acquired themes include unity of command, trustee, commitment, capacity prosperity, align strategy, information synergy, knowledge enhancement, sustainable security, justice clarity, land use planning, climate change adaptation, environment reform, wisdom, environment, diplomacy, capacity and coherence. CONCLUSIONS: Disaster good governance is strengthened by the trustee, commitment, capacity prosperity, align strategy, and organize. Information synergy and knowledge enhancement are effective in the culture of prevention. Collective wisdom, diplomacy, and capacity coherence raise the alignment of public organizations and the government in the risk management process.